WLAN Integrated with GPRS Network Securely - Abdalla, Mohammed A.; Salim, Khalifa A.; Mohammed, Zinah Jaafar (Al-Khwarizmi Engineering Journal, 2012)
In this paper a WLAN network that accesses the Internet through a GPRS network was implemented and tested. The proposed network is managed by the Linux based server. Because of the limited facilities of GPRS such as dynamic IP addressing besides to its limited bandwidth a number of techniques are implemented to overcome these limitations.      Dynamic Host Configuration Protocol (DHCP) server was added to provide a single central control for all TCP/IP resources. Squid Proxy  was added to provide caching of the redundant accessed Web content to reduce the Internet bandwidth usage and speeding up the client’s download time. Network Address Translation (NAT) service was configured to share one IP address among several different systems. In order to accomplish a secure channel to exchange data between two network devices, the Secure Shell (SSH) protocol was added.The first test shows that the data transfer rate at different time intervals of the day found to be an average of 10.95 Kbps for uploading and 13.7 Kbps for downloading and the second test shows that the network performance improved when squid proxy cache was used. The data rate found to be 143.3 Kbps average for uploading rate and 376.6 Kbps average for downloading rate.